Polymorphism T3111C of the Clock gene in ethnic groups of women from Russia and Buryatia - O. V. Kaluzhnaya; N. V. Semenova; T. A. Bairova; I. M. Madaeva; E. V. Belyaeva; L. I. Kolesnikova (Вавиловский журнал генетики и селекции)
Biological rhythms of organisms depend on both changing conditions of the external environment and internal “biological clock”. Circadian rhythms are the response of the organism to the change of day and night. They are some of the most important biological rhythms of organisms. Circadian rhythms are regulated by the group of circadian genes. It is known that women suffer from sleep disorders more often than men. Up to 50 % of menopausal women complain of problems associated with sleeping. The study involved 403 menopausal women aged from 45 to 60 years: 214 Russians (the average age is 52.74±6.28 years) and 189 Buryats (the average age is 51.95±5.13 years) living in Eastern Siberia (Irkutsk region, Irkutsk and Republic of Buryatia, Ulan-Ude). The prevalence of genotypes and alleles of the polymorphism T3111C of the circadian rhythm gene Clock (rs1801260) was studied in these groups. To this end, we conducted genotyping of DNA samples by polymerase chain reaction. It was shown that the compared groups have statistically significant differences in genotypes frequency (р = 0.001). It was found that in the group of Russian women the frequency of the TC genotype (p = 0.004) was significantly higher and the frequency of the TT genotype (p = 0.0001) was significantly lower than those in the sample of women of Buryatia. It was shown that in the group of Russian women allele 3111C is found in 30.4 % of cases, which is statistically significantly more often than in the group of Buryat women, where the frequency of allele 3111C was 19.3 % (p = 0.014).